The Teachers' Perceptions of the Effectiveness of Using Virtual Learning Media - Abd Ghofur (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2021)
This study aims to explore teachers' perceptions of the effectiveness of using virtual learning media. The research method used is descriptive quantitative research to determine the description of teacher perceptions of the effectiveness of using virtual learning media during the Covid-19 pandemic. Respondents in this study were 813 teachers from kindergarten, elementary, junior high school, high school levels spread across several regions in Indonesia. The data collection technique used is a questionnaire or questionnaire that is distributed to respondents through online surveys (using the google form application). The results showed that 97% of teachers said that their educational institutions had implemented virtual-based learning. The effectiveness of learning using virtual learning media was recognized by 44% of teachers. Several types of virtual media are used by teachers, including those using Google Classroom, Edmodo, Telegram, Email, WhatsApp (WA) and several other applications. Penelitian ini bertujuan untuk menggali persepsi guru terhadap efektivitas penggunaan media pembelajaran virtual. Metode penelitian yang digunakan adalah penelitian kuantitatif deskriptif untuk mengetahui gambaran persepsi guru terhadap efektivitas penggunaan media pembelajaran virtual selama masa pandemi covid-19 ini. Responden dalam penelitian ini adalah 813 orang guru mulai dari jenjang TK, SD, SMP, SMA yang tersebar di beberapa daerah yang ada di Indonesia. Teknik pengumpulan data yang digunakan yakni kuesioner atau angket yang disebarkan kepada responden melalui survei secara daring (menggunakan aplikasi google form). Hasil penelitian menunjukkan bahwa 97% guru mengatakan kalau lembaga pendidikannya telah menerapkan pembelajaran berbasis virtual. Efektivitas pembelajaran dengan menggunakan media pembelajaran virtual diakui oleh sebanyak 44% guru. Beberapa jenis media virtual yang digunakan oleh guru di antaranya ada yang menggunakan google classroom, edmodo, telegram, email, whatsapp dan beberapa aplikasi lain.